Educators’ Perspectives on Using (AI) As A Content Creation Tool in Libyan Higher Education: A Case Study of The University of Zawia - Baroud, Najah; Alouzi, Khuloud; Elfzzani, Zenab; Ayad, Nahid; Albshkar, Hajer (JERIT: Journal of Educational Research and Innovation Technology, 2024)
This study investigates how artificial intelligence (AI) is incorporated into curriculum development and instruction at the University of Zawia in Libya. It focuses on focuses on educators’ challenges, perceptions, and their use of (AI) for content creation. According to 119 participants in a mixed-methods study incorporating quantitative questionnaire and qualitative interviews, 96.4% acknowledge the need for advanced training, and 95.2% believe that (AI) will have an increasing impact on education. Even though 71.9% of respondents agreed that (AI) could improve educational materials, only 30.2% utilized (AI) tools to assess students. Challenges included limited access to (AI) tools (79.6% had not attended (AI) workshops) and ethical concerns (61.3%). Notwithstanding these obstacles, academics emphasized how (AI) could improve research and instruction. They also highlight the necessity of institutional support and training to maximize (AI’s) contribution to higher education.